Phleboscore in chronic venous disease - Mulki, Siddharth; Mascarenhas, Rupa Merlyn; Salutagi, Naveen Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Chronic venous disease (CVD) is a multifactorial condition affecting among populations worldwide. The symptoms appear early in the progression of the disease and as the time progresses the severity of the disease increases. Thus a proper clinical management tool is essential to prevent potential harms of the disease, which also entails a significant loss of the quality of life in these individuals. The aim of the present study is to make use of the tool phleboscore for the patients with lower limb problems to quantify the risk of developing CVD complications. Methods: A prospective observational study with 2788 patients with lower limb complaints of venous disease was conducted in the out-patient department at A. J. Institute of medical sciences, Mangalore. Patients were asked about the symptoms of the venous diseases like sensation in the limb, any changes in the limb. The patients with two or more symptoms were assessed with phleboscore questions. Based on the phleboscore a descriptive analysis of the collected data was done. Results: With regards to the phleboscore patients were divided into three classes; low risk, moderate risk and high risk. Almost 73.6% patients were at medium risk of developing CVD. 7.6% patients at high risk. 63.5% of patients with sedentary lifestyle were at medium risk. Conclusions: Phleboscore is an essential tool to assess the potential risk of patients developing CVD. This tool helps in early identification of patients who are about to go into high risk group and help them by early interventions to prevent the development of more serious disease.